Heating affects protein digestion of skimmed goat milk under simulated infant conditions. (15th February 2023) - Ren, Qing; Boiani, Mattia; He, Tao; Wichers, Harry J.; Hettinga, Kasper A.
Highlights: The digestion was studied from supernatant and gastric clot perspectives. The effects of heating on digestion of goat milk depend on the specific temperature. Digestion of 65 °C heated samples showed the highest intensity of bioactive peptides. Heating higher than 75 °C induced further cleavage of bioactive peptides. Abstract: The objective of this research was to analyse the effects of heating on digestion of skimmed goat milk proteins. Most previous goat milk digestion studies evaluated the digestion only based on the supernatant. In this study, digestion of skimmed goat milk was studied in both supernatant and gastric clot. The results indicated that, compared to mild temperature heated samples (≤75 °C), samples heated at ≥80 °C showed more extensive gastric clot formation with a higher protein digestion rate, but also resulted in a larger amount of undigested whey proteins due to its severe aggregation. For the peptidome, β-casein was the major source of bioactive peptides. The samples heated at 65 °C showed higher bioactive peptide abundances, whereas at temperatures higher than 75 °C, it was reduced due to cleavage into smaller peptides. Overall, this study showed that different heating temperatures induced different whey protein denaturation degrees, which affected their digestion in skimmed goat milk..